Dysregulated lactate metabolism synergizes with ALS genetic risk factors to accelerate motor decline - Shweta Tendulkar; Tong Wu; Amy Strickland; Amber R. Hackett; Yurie Sato-Yamada; Xianrong Mao; Yo Sasaki; Jeffrey Milbrandt; A. Joseph Bloom; Aaron DiAntonio (PLoS ONE, 2026)
Neurons rely on glial ‘lactate shuttling’ for metabolic support, which declines with aging and in neurodegenerative disease. Full disruption of lactate shuttling in peripheral nerves causes progressive axon degeneration, but we were interested to understand how partial disruption, a scenario more relevant to aging and disease, contributes to neurodegeneration risk. Pyruvate and lactate are interconverted by lactate dehydrogenases (LDHA and LDHB) in both lactate producing and consuming cells. We therefore began by investigating Ldhb knockout mice (loss of LDHA, the dominant LDH in liver and muscle, caused embryonic lethality), and discovered that they develop progressive neuromuscular junction atrophy and functional decline without axon degeneration. Because even Ldhb + /- heterozygosity significantly affects motor behavior, we also wondered about a potential link to congenital disease and pursued this by identifying rare loss-of-function LDHB variants among ALS patients. Next, to better understand how LDHB loss leads to motor decline, we selectively deleted it in defined cell types. Schwann cell (SC)-specific deletion caused robust motor defects, whereas motor neuron–specific deletion has little effect. Reasoning that neuronal LDHB deficiency could model age-associated decline in lactate metabolism, we asked whether it would interact with ALS genetic risk. Indeed, motor-neuron LDHB deficiency synergizes with relatively mild ALS risk variants— TDP43 Q331K and Sod1 D83G knock-in alleles—to produce early motor neuropathy, indicating that LDHB loss enhances disease risk. These findings establish lactate metabolism as a modifier of motor system vulnerability and highlight it as a therapeutic target in peripheral as well as central neurodegeneration.